Family ties, knots and gaps: Mapping the linked lives principles in the family and life course literature - Carvalho, D.; Nico, M.; Carvalho, H. (Marriage and Family Review, 2023)
Linked lives, recognizing the interdependent nature of lives, is one of the principles of the life course perspective, particularly appraised in the context of family and intergenerational relations. It has been used as a consensual general premise, although empirically underexplored. As a consequence, its contribution has been limited. Therefore, we aimed to understand how this principle, within family relations, has been researched by carrying out a systematic collection and multivariate analysis of bibliographical references (N = 507). We identified three profiles of publications: Theoretical Holistic; Nuclear Family Qualitative; and Contemporary Expansion. This recent development reflects a greater diversification of theoretical, thematic and methodological approaches. However, there is a continued prevalence of unidirectional, intergenerational and top-down family links, and room for improvement in cross-comparative and methodological perspectives.